1994
DOI: 10.1021/bi00197a039
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting Catalytic Roles for Aspartate Residues in Phosphoribulokinase

Abstract: The DNA encoding Rhodobacter sphaeroides phosphoribulokinase (PRK) has been modified to allow ligation into pET-3d. Using the resulting expression plasmid, PRK was overexpressed in Escherichia coli and isolated in milligram quantities. Homogeneous preparations of the enzyme exhibit properties comparable to those of PRK expressed using a previously described pUC19-derived construct [Sandbaken et al., Biochemistry 31, 3715-3719]. Mutagenesis experiments have been designed to produce conservative substitutions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 43 publications
2
56
0
Order By: Relevance
“…A function in liganding to M values increase by Ϸ20-fold for ATP and Ϸ40-fold for mevalonate. Effects of this magnitude have been observed upon replacement of carboxyl groups that function as cation ligands in phosphofructokinase (25), 6-phosphofructo-2-kinase (22), and phosphoribulokinase (26). If the assignment of Glu-193 as cation ligand is correct, then, in the absence of any other invariant acidic residues that can be clearly be implicated in catalysis, a serine/threonine residue would be a plausible candidate for the role of second cation ligand.…”
Section: An Active Site Serine In Mevalonate Kinasementioning
confidence: 99%
“…A function in liganding to M values increase by Ϸ20-fold for ATP and Ϸ40-fold for mevalonate. Effects of this magnitude have been observed upon replacement of carboxyl groups that function as cation ligands in phosphofructokinase (25), 6-phosphofructo-2-kinase (22), and phosphoribulokinase (26). If the assignment of Glu-193 as cation ligand is correct, then, in the absence of any other invariant acidic residues that can be clearly be implicated in catalysis, a serine/threonine residue would be a plausible candidate for the role of second cation ligand.…”
Section: An Active Site Serine In Mevalonate Kinasementioning
confidence: 99%
“…This precedent is based on mutagenesis experiments on phosphofructokinase (23,24), human hexokinase (25), and phosphoribulokinase (26), as well as on analysis of the crystal structure of glycerol kinase (27). Carboxylates have also been implicated as ligands to the cation of the MgATP substrates of these and other phosphotransferases, such as 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (28) and adenylate kinase (29).…”
Section: Isolation Of Human Mevalonatementioning
confidence: 99%
“…With the objective of facilitating the identification of catalytic residues, our lab developed a PET-3d based system (Charlier et al, 1994) to express in E. coli the PRK I-encoding DNA that had been provided by Hallenbeck and Kaplan (1 987). Anticipating that large diminutions in activity would be encountered if we successfully replaced amino acids crucial to reaction chemistry, the expression system would, at a minimum, be required to produce large amounts of PRK protein to support assays.…”
Section: A Overexpression Of R Sphaeroides Prkmentioning
confidence: 99%
“…Despite these legitimate concerns, our lab proposed that H135, K165, R168, R173, and R187 (prokaryotic PRK numbering) should be included with H45 and R49 on the roster of absolutely invariant basic residues in PRK. Previous work (Charlier et al, 1994) had suggested that H135, located within PRKs "Walker B ' motif, was not crucial to substrate binding or Figure 6. Structural representation of the active site of phosphoribulokinase (PRK).…”
Section: Selection Of Mutagenesis Targets and Interpretation Of Mumentioning
confidence: 99%
See 1 more Smart Citation